Challenges in the Enforcement of Animal Protection Laws in Singapore - SEE, Alvin W. L. (Institutional Knowledge at Singapore Management University, 2014)
Singapore has fairly powerful animal protection laws. In practice, however, these laws are only powerful to the extent that they are actually enforced. In Singapore, the low number of prosecutions for animal cruelty is a cause for serious concern. While there can be a myriad of reasons for this phenomenon, this paper argues that one primary cause is the insufficient understanding of what amounts, or may amount, to cruelty at law. This results in an unsound enforcement policy which reduces the protection afforded to animals. By highlighting this problem, this paper hopes to draw attention to the importance of the study and development of animal law, which has a direct impact on the extent to which animals are actually protected.